Проза 1920-1940-х годов: [сборник : в 3 томах] (Институт "Открытое общество" ; [составитель Н. В. Корниенко]) - Корниенко Н. В. (Пушкинская библиотека, 2001)
Экземпляры: (20181106) / Инвентарный номер: 1832 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: П 79 / ББК: 84(2Рос=Рус)6-4